PHP web services : working with APIs and PHP - Mitchell, Lorna Jane (O'Reilly Media, 2014)
"Learn how to build web services with PHP and exchange data across applications. In this video course, web development consultant Lorna Jane Mitchell provides real-world examples and advice based on her extensive experience to guide you through the key API concepts."--Resource description page.